Effects of glycaemic control on memory performance, hippocampal volumes and depressive symptomology - Yatagan Sevim, Gulin; Alkan, Erkan; Taporoski, Tamara P.; Krieger, Jose E; Pereira, Alex C; Evans, Simon L. (Diabetology and metabolic syndrome, 2024)
Background Diabetes and poor glycaemic control have been shown to negatively impact cognitive abilities, while also raising risk of both mood disorders and brain structural atrophy. Sites of atrophy include the hippocampus, which has been implicated in both memory performance and depression. The current study set out to better characterise the associations between poor glycaemic control, memory performance, and depression symptoms, and investigate whether loss of hippocampal volume could represent a neuropathological mechanism underlying these. Methods 1331 participants (60.9% female, age range 18–88 (Mean = 44.02), 6.5% with likely diabetes) provided HbA1c data (as an index of glycaemic control), completed a word list learning task, and a validated depression scale. A subsample of 392 participants underwent structural MRI; hippocampal volumes were extracted using FreeSurfer. Results Partial correlation analyses (controlling for age, gender, and education) showed that, in the full sample, poorer glycaemic control was related to lower word list memory performance. In the MRI sub-sample, poorer glycaemic control was related to higher depressive symptoms, and lower hippocampal volumes. Total hippocampus volume partially mediated the association between HbA1c levels and depressive symptoms. Conclusions Results emphasise the impact of glycaemic control on memory, depression and hippocampal volume and suggest hippocampal volume loss could be a pathophysiological mechanism underlying the link between HbA1c and depression risk; inflammatory and stress-hormone related processes might have a role in this.